Thor's Microsoft security bible : a collection of practical security techniques - Mullen, Timothy M. (Syngress/Elsevier, 2011)
"Thor?s Microsoft Security Bible provides a "one-stop-shop" for Microsoft-related security techniques and procedures as applied to the typical deployment of a Microsoft-based infrastructure. The book contains detailed security concepts and methodologies described at every level: Server, Client, Organizational Structure, Platform-specific security options, application specific security (IIS, SQL, Active Directory, etc.) and also includes new, never-before-published security tools complete with source code" - Syngress website